Feasibility analysis and study of an intrahepatic portal vein infection hepatic alveolar echinococcosis C57 mouse model - Tian, Weili; Ji, Wenchao; Li, Jun; Liu, Wenya; Wen, Zhi; Wu, Juan (Frontiers in Veterinary Science, 2022)
Objective: To establish and study an intrahepatic portal vein infection hepatic alveolar echinococcosis (HAE) C57 mouse model and provide a theoretical basis for clinical research on HAE. Methods: A number of C57 mice were used to establish the HAE mouse model. The location, size, morphology, appearance and pathological changes in the liver lesions in different groups were characterised using ultrasound, magnetic resonance imaging (MRI) and haematoxylin and eosin staining. Results: The mortality rate of the C57 mice was 20%, and the success rate of infection was 75%. The abdominal ultrasound images and MRIs clearly indicated the location, size, shape and appearance of the liver lesions and the relationship between the lesions and the adjacent organs. The size, morphology and signal of the livers in the control group were normal. The pathological results of the experimental group indicated a hepatic vesicular acinar cyst, while the control group exhibited normal livers. Conclusion: The intrahepatic portal vein infection HAE mouse model was successfully established.